NATO in the Arctic: incentives and impediments - Dmitry A. Danilov (Научно-аналитический вестник Института Европы РАН)
The escalating geopolitical confrontation between the Euro-Atlantic and Russia fundamentally determines the Arctic agenda. The security dilemma in the Arctic, which was previously considered in the paradigm of the common interest of non-militarization and cooperation, is becoming rather more acute. The changing approaches of Arctic actors to defining security policy are changing dramatically, primarily in all countries that have formed the Arctic Council (AC), especially after Finland and Sweden joining in NATO. Russia is faced not only with Western Arctic players’ attempts to push it away from planning and implementing a multilateral Arctic policy, but also with growing risks of violating the existing strategic stability and balances in the Northern Arctic area. The article examines the dilemmas of NATO’s activation in the High North. It is shown that the factors that hampered the framing by the alliance of a collective Arctic strategy retain their significant impact. However, the motivation for NATO’s activation there is noticeably increasing, and the NATO/Arctic discourse is becoming increasingly substantive. The U.S. is strengthening military cooperation with its northern allies, including the new ones, on a bilateral basis, but keeps open a window of opportunity to strengthen NATO as an organization in the Arctic.